Bisphenol A (BPA) acts as an endocrine disruptor in women with Polycystic Ovary Syndrome: Hormonal and metabolic evaluation - Kawa, Iram Ashaq; Masood, Akbar; Ganie, Mohd Ashraf; Fatima, Qudsia; Jeelani, Humira; Manzoor, Saika; Rizvi, Syeed Masuma; Muzamil, Mohd; Rashid, Fouzia (Obesity medicine, 2019)
To assess the serum Bisphenol A levels in women with Polycystic Ovary Syndrome (PCOS) and its possible association with their hormonal, metabolic and hematological parameters. A total of 49 women with PCOS and 39 healthy controls were included in the study. The diagnosis of PCOS was done using the Rotterdam criteria 2003. Anthropometric and clinical baseline profile of all the study subjects was done. Serum BPA levels were estimated and its correlation with hormonal, metabolic and hematological parameters was investigated. The women with PCOS demonstrated higher levels of BPA as compared to healthy women (26.4 ± 14.9 versus 18.95 ± 8.88 ng/ml; p = 0.0046). A significant association of clinical features like BMI (r = 0.296, p = 0.039), Waist circumference (r = 0.315, p = 0.027) and waist-hip ratio (r = 0.402, p = 0.004) with BPA was found. The BPA levels are also strongly associated with testosterone levels and with the biochemical abnormalities describing the syndrome (Blood glucose-Fasting (r = 0.478, p = 0.001), Blood glucose-1 hour (r = 0.307, p = 0.032), Blood glucose-2 hour (r = 0.393, p = 0.005), total cholesterol (r = 0.361, p = 0.011), triglycerides (r = 0.362, p = 0.011), Insulin fasting (r = 0.426, p = 0.002), HOMA-IR (r = 0.543, p=<0.0001), QUICKI (r = −0.459, p = 0.0009). BPA was also positively correlated with erythrocyte parameters like HCT (r = 0.284, p = 0.048) and MCV (r = 0.360, p = 0.011). The present study suggests that BPA an endocrine disruptor plays an important role in the pathogenesis of PCOS and contributes in the development and phenotype of PCOS.